Calprotectin as a marker of inflammation in cystic fibrosis. Issue 2 (February 1996) - Golden, B E; Clohessy, P A; Russell, G; Fagerhol, M K
Abstract : Calprotectin is an abundant neutrophil cytosolic protein released during neutrophil activation or death. The use of plasma calprotectin concentration as a marker of pulmonary inflammation was tested in 31 children with cystic fibrosis, none of whom was acutely unwell or pyrexic. Twenty three were receiving antibiotics, 21 had positive sputum cultures, but none of the traditional tests clearly diagnosed ongoing infection. Plasma calprotectin was significantly higher in the cystic fibrosis group than in matched controls. Sixteen children with cystic fibrosis had values above the control range (320-1570 micrograms/l). Their chest radiograph Northern score, an index of accumulated pulmonary involvement, and their plasma copper, an index of acute phase response, both correlated with plasma calprotectin. Plasma gamma-glutamyltransferase also correlated weakly with plasma calprotectin: thus, hepatic pathology may be a confounding variable. However, the data still suggested that plasma calprotectin is a better index of inflammation than the traditional indices in general use.